Effects of two growth regulators on yield and yield attributes of two varieties of wheat (Triticum aestivum L.) (Bangladesh Journal of Botany, 2010)
Foliar applications of 500 and 1000 ppm KNap and 2 and 4 ppm mixtalol on Kanchan and Akbar varieties of wheat showed that in most cases spikelets per plant, grains per spikelet, weight of 1000 grains and grain yield per plant increased significantly. In Kanchan the highest yield was due to 4 ppm mixtalol and in Akbar it was due to 500 ppm KNap. Key words: KNap; Mixtalol; Yield attributes; Wheat; Foliar application DOI: 10.3329/bjb.v39i1.5539Bangladesh J. Bot. 39(1): 127-129, 2010 (June)